2011
DOI: 10.3892/mmr.2011.539
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone suppresses oxidative stress via androgen receptor-independent pathway in murine cardiomyocytes

Abstract: Abstract. Evidence supports that oxidative stress exerts significant effects on the pathogenesis of heart dysfunction. On the other hand, the presence of specific androgen receptor (AR) in mammalian cardiomyocytes implies that androgen plays a physiological role in cardiac function, myocardial injury and the regulation of the redox state in the heart. This study used the testicular feminized (Tfm) and castrated male mice to investigate the effects of testosterone deficiency, physiological testosterone therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…In a recent animal study, a regimen of testosterone administration and simultaneous low-intensity physical training was found to improve skeletal muscle mitochondrial biogenesis and mitochondrial quality control in elderly male mice, suggesting the importance of maintaining proper testosterone levels for muscle metabolism ( 51 ). In various cellular models, mainly of prostate cancer cells, low levels of testosterone were found to be associated with oxidative stress induced by decreased antioxidant levels via decreased expression of antioxidant enzymes such as SOD, GSH-Px, and catalase ( 52 ). Whereas, testosterone deficiency has been observed to induce oxidative stress in cardiomyocytes, testosterone replacement therapy (TRT) has been found capable of suppressing oxidative stress mediated via the androgen receptor-independent pathway ( 52 ).…”
Section: Cellular and Molecular Mechanisms Underlying Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent animal study, a regimen of testosterone administration and simultaneous low-intensity physical training was found to improve skeletal muscle mitochondrial biogenesis and mitochondrial quality control in elderly male mice, suggesting the importance of maintaining proper testosterone levels for muscle metabolism ( 51 ). In various cellular models, mainly of prostate cancer cells, low levels of testosterone were found to be associated with oxidative stress induced by decreased antioxidant levels via decreased expression of antioxidant enzymes such as SOD, GSH-Px, and catalase ( 52 ). Whereas, testosterone deficiency has been observed to induce oxidative stress in cardiomyocytes, testosterone replacement therapy (TRT) has been found capable of suppressing oxidative stress mediated via the androgen receptor-independent pathway ( 52 ).…”
Section: Cellular and Molecular Mechanisms Underlying Sarcopeniamentioning
confidence: 99%
“…In various cellular models, mainly of prostate cancer cells, low levels of testosterone were found to be associated with oxidative stress induced by decreased antioxidant levels via decreased expression of antioxidant enzymes such as SOD, GSH-Px, and catalase ( 52 ). Whereas, testosterone deficiency has been observed to induce oxidative stress in cardiomyocytes, testosterone replacement therapy (TRT) has been found capable of suppressing oxidative stress mediated via the androgen receptor-independent pathway ( 52 ).…”
Section: Cellular and Molecular Mechanisms Underlying Sarcopeniamentioning
confidence: 99%
“…The association between oxidative stress and testosterone is controversial. Some basic studies have indicated that testosterone suppresses oxidative stress [ 35 , 36 ]. In contrast, other studies reported that testosterone promotes oxidative stress [ 37 - 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In various cellular models, mainly of prostate cancer cells, low levels of testosterone were found to be associated with oxidative stress induced by decreased antioxidant levels via decreased expression of antioxidant enzymes such as SOD, GSHPx, and catalase (52). Whereas, testosterone deficiency has been observed to induce oxidative stress in cardiomyocytes, testosterone replacement therapy (TRT) has been found capable of suppressing oxidative stress mediated via the androgen receptor-independent pathway (52).…”
Section: Mitochondrial Malfunction and Oxidative Stressmentioning
confidence: 99%
“…In a recent animal study, a regimen of testosterone administration and simultaneous low-intensity physical training was found to improve skeletal muscle mitochondrial biogenesis and mitochondrial quality control in elderly male mice, suggesting the importance of maintaining proper testosterone levels for muscle metabolism (51). In various cellular models, mainly of prostate cancer cells, low levels of testosterone were found to be associated with oxidative stress induced by decreased antioxidant levels via decreased expression of antioxidant enzymes such as SOD, GSHPx, and catalase (52). Whereas, testosterone deficiency has been observed to induce oxidative stress in cardiomyocytes, testosterone replacement therapy (TRT) has been found capable of suppressing oxidative stress mediated via the androgen receptor-independent pathway (52).…”
Section: Mitochondrial Malfunction and Oxidative Stressmentioning
confidence: 99%